2014
DOI: 10.4028/www.scientific.net/amr.974.389
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Bone Cutting Force with FEM

Abstract: In orthopedic surgery, it is easy to do harm to surrounding tissues, so the study of bone cutting is necessary. In this article, a finite element model (FEM) of orthogonal bone cutting is developed. Cutting force intra-operatively can provide the surgeon with additional on-line information to support him to control quality of cutting surface. The obtained cutting force decreased little with cutting speed increasing, but ascended evidently with cutting depth increasing. The results of finite element simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…One study focused on assessing surface quality as an essential parameter of bone tissue treatment. Research focusing on evaluating the cutting force of bone tissue using FEM was presented by Liu et al [ 17 ], with similar results to other authors. Depending on the cutting speed value (600–1000 mm/s), cutting force was at the level of 11–12 N. Depending on the cutting depth (0.1–0.5 mm), the increase in cutting force was more significant and amounted to 5–15 N. These results indicate that the FEM analysis reflects the actual experimental results.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…One study focused on assessing surface quality as an essential parameter of bone tissue treatment. Research focusing on evaluating the cutting force of bone tissue using FEM was presented by Liu et al [ 17 ], with similar results to other authors. Depending on the cutting speed value (600–1000 mm/s), cutting force was at the level of 11–12 N. Depending on the cutting depth (0.1–0.5 mm), the increase in cutting force was more significant and amounted to 5–15 N. These results indicate that the FEM analysis reflects the actual experimental results.…”
Section: Introductionsupporting
confidence: 69%
“… Comparison of cutting force for the tested tool and data from the literature [ 2 , 9 , 15 , 17 , 63 ]. …”
Section: Figurementioning
confidence: 99%
“…It can be better used to assist robotic surgery, optimize cutting parameters, and guide the design of orthopedic surgical tools. Liu [ 9 ] obtained the influence of spindle speed, feed rate, and cutting depth on cutting force through cortical bone milling experiments. It was found that as the spindle speed increased, the cutting force decreased, while the feed rate and cutting depth showed a positive correlation.…”
Section: Introductionmentioning
confidence: 99%